Penerapan Pembelajaran Dengan Metode Inkuiri Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 025 Tambusai Utara Tahun Pelajaran 2015/2016 - Hidayat Hidayat (Indonesian Journal of Basic Education, 2018)
Classroom action research by applying the inquiry method in the fourth grade mathematics lessons SDN 025 Tambuasai Utara, this research was carried out to improve student learning outcomes with 25 students. This research was carried out in two cycles. Each cycle consists of two meetings. Each cycle consists of 4 (four) stages, namely: (1) Improvement Plan, (2) Implementation of Improvement, (3) Data Collection, (4) Reflection. Student learning outcomes before the study still did not reach KKM with an average of 58.8 with 38% completeness percentage. After an action occurs there is an increase in student learning outcomes that is on average in cycle I 67.7 with a percentage of completeness 62%. Whereas in cycle II obtained the average student learning outcomes amounted to 73.5 with 92% completeness percentage, this shows active students when implementing learning with the inquiry method. From the results of the study it can be concluded that the results of the application of the inquiry method in learning can improve the mathematics learning outcomes of the fourth grade students of SDN 025 Tambusai Utara.